Novel pectic-dominated cell wall polysaccharides from fresh Rehmannia radix: Physicochemical and rheological characteristics, antioxidant-immunomodulation dual activities, and structure-activity relationship analysis - Yupeng Yang; Manli Zhang; Hongxu Ma; Chaoyang Lin; Zongji Wang; Bingji Ma; Li Wang (Food Bioscience, 2026)

Co NPs@N-Doped Peanut Shell-derived Biochar As an Efficient Catalyst for Peroxymonosulfate Activation in Acetaminophen Degradation - Xiaoxin Chen; Xingzi Zhu; Caiyan Ge; Jinxin Wang; Manli Guo; Yujuan Cao; Bixia Lin (Water, Air, & Soil Pollution, 2026)

Impact of air pollution control strategies on full-phase chlorine species emissions from coal-fired power plants in China during 2013-2022 - Yuying Tang; Yulong Yan; Xionghui Qiu; Zhijian Li; Manli Wang; Zhen Li; Minneng Wen; Wenyi Jin; Yuyang Cheng; Lin Peng (Atmospheric Environment, 2026)

Identifying the genesis and evolution of geothermal water in the coal mining area, North China: Insights from hydrochemistry and δ2H, δ18O, δ13C, δ34S and 87Sr/86Sr isotopes - Jie Zhang; Herong Gui; Luwang Chen; Manli Lin; Huifang Rong; Jun Li; Ruirui Li; Mingda Cao (Geothermics, 2026)

Molecular mechanisms of bone metastasis in breast cancer based on transcriptomic and microbiomic analysis - Dihui Zhang; Manli Long; Lingcui Meng; Yongjin Li; Bolai Chen; Dingkun Lin; Guoyi Su (Cancer Causes & Control, 2025)

Exercise Training Promotes Neural Remodeling and Vascular Regeneration in Cerebral Ischemic Rats Through the JNK/c-jun Signaling Pathway - Zijun Zhao; Xiuyun Chen; Zezhong Zhuang; Jianmin Chen; Zhijian Zheng; Wenwen Wu; Zhiyun Wu; Qiang Lin; Manli Chen; Ji Liu; Nan Liu; Ronghua Chen; et al. (Molecular Neurobiology, 2025)

Establishment and application of environmental geochemical baseline of soil PTEs in a typical metal mining area: a case study of the Xinqiao mining area in Tongling city, Anhui province, China - Jun Zhang; Manli Lin; Herong Gui; Song Chen; Xianghong Liu; Meiping Wu; Xinrui Huang; Li Ma; Weihua Peng (Journal of Soils and Sediments, 2025)

Ratiometric fluorescence analysis of tetracycline by dual-ligand europium-based metal-organic framework - Yating Zhong; Keying Zhang; Xinru Wang; Haibo Liang; Ying Yu; Manli Guo; Yujuan Cao; Bixia Lin (Food Chemistry, 2025)

Depositional evolution and sedimentary response to sea level changes of the lower Cambrian carbonate platform of the Wusonggeer Formation, Tarim Basin, northwest China - Xuqiao Wu; Changsong Lin; Wenfang Yuan; Hao Li; Xianzhang Yang; Fan Xu; Manli Zhang; Xiangyu Liu (Marine and Petroleum Geology, 2025)

Long-term exposure to ambient air pollution and the incidence of systemic lupus erythematosus - Lihong Ye; Ding Ye; Yu Qian; Jiayu Li; Bin Liu; Jiacheng Ying; Manli Wang; Hao Lin; Jing Guo; Xiaohui Sun; Zhixing He; Chengping Wen; et al. (Chemosphere, 2025)

Construction of Zinc-based metal-organic frameworks for visual ratiometric fluorescence detection of tetracycline - Yating Zhong; Haocheng Gao; Jingqi Yang; Xinru Wang; Ying Yu; Yujuan Cao; Manli Guo; Bixia Lin (Analytica Chimica Acta, 2025)

Tracing potentially toxic elements in button mushroom cultivation and environmental implications: Insights via stable lead (Pb) isotope analysis - Xun Liu; Junjie Yu; Xueping Lu; Manli Yang; Yazhou Liu; Hui Sun; Ying Ni; Guo Lin; Chuansheng Wu; Jun Tang (Journal of Cleaner Production, 2024)

Preclinical evaluation of RQ3013, a broad-spectrum mRNA vaccine against SARS-CoV-2 variants - Shudan Tan; Jinghua Zhao; Xue Hu; Yufeng Li; Zihan Wu; Guoliang Lu; Zhaoli Yu; Binhe Du; Yan Liu; Li Li; Yuchen Chen; Ye Li; et al. (Science Bulletin, 2023)

Regime Shifts in the Damage Caused by Tropical Cyclones in the Guangdong–Hong Kong–Macao Greater Bay Area of China - Manli Zheng; Lin Mu; Wenjuan Li; Fei Wang; Yan Li (Journal of Marine Science and Engineering, 2023)
Tropical cyclones (TCs) pose a significant threat in terms of wind-induced damage and storm risk to the Guangdong–Hong Kong–Macao Greater Bay Area (GBA) of China. In this research, annual power dissipation index (PDI) and storm surge and wave destructive potential (SDP) index from June to November were used to estimate the damage caused by the TC events in the buffer zone of the GBA. The regime shifts in 1993 and 2013 were identified through the Bayesian changepoint detection in six TC datasets. The TC-induced damage during 1994–2012 (the low-damage period) was weaker than that in 1977–1993 and 2013–2020 (the high-damage periods). The intensity and size of stronger TCs are the dominant factors responsible for the interdecadal changes in the TC damage. This may be explained by the influences of sea surface temperature (SST), surface latent heat flux and mid-level relative humidity. During high-damage periods, TCs can extract more energy from the ocean, leading to increased TC intensity and larger size. Conversely, during low-damage periods, TCs undergo a decrease in energy intake, resulting in reduced TC power and smaller size. The variations in the SST are relative to the Luzon Strait transport. In addition, the reduction in TC translation speed is unfavorable for the development of TCs in low-damage periods. Further research suggested that mid-level steering flow affects the TC movement velocity. The results offer valuable insights into the variations in the TC-induced damage in the GBA.

A Facile, Label-free and Versatile Fluorescence Sensing Nanoplatform Based on Titanium Carbide Nanosheets for the Detection of Various Targets - Meishuang Liang; Bixia Lin; Zhijiao Tang; Li Zhang; Manli Guo; Yujuan Cao; Yumin Wang; Ying Yu (Journal of Fluorescence, 2022)

Bone marrow-derived mesenchymal stem cells improve post-ischemia neurological function in rats via the PI3K/AKT/GSK-3β/CRMP-2 pathway - Xiaohui Lin; Hongbin Chen; Manli Chen; Ting Li; Yongxing Lai; Longzai Lin; Peiqiang Lin; Ji Liu; Yixian Zhang; Ronghua Chen; Houwei Du; Xinhong Jiang; et al. (Molecular and Cellular Biochemistry, 2021)

Efficient electrokinetic remediation of heavy metals from MSWI fly ash using approaching anode integrated with permeable reactive barrier - Huilin Li; Yi Zheng; Lin Yu; Huirong Lin; Manli Zhang; Binquan Jiao; YanChyuan Shiau; Dongwei Li (Environmental Science and Pollution Research, 2021)

Depositional sequences and microfacies of Lower Carboniferous strata in the Marsel block of the Chu-Sarysu Basin, Southern Kazakhstan - Yuan Wang; Changsong Lin; Yanda Sun; Jingyan Liu; Hao Li; Haiquan He; Qinglong Wang; Muye Ji; Manli Zhang; Bozhi Zhao; Zhiyuan Zhang (Carbonates and Evaporites, 2020)

Microbiological analysis of cadmium-contaminated sediments during biostabilization with indigenous sulfate-reducing bacteria - Weihua Peng; Xiaomin Li; Manli Lin; Wenhong Fan (Journal of Soils and Sediments, 2020)

Comparison of monoculture and mixed culture (Scenedesmus obliquus and wild algae) for C, N, and P removal and lipid production - Zhi Qu; Pengfei Duan; Xubing Cao; Manli Liu; Li Lin; Ming Li (Environmental Science and Pollution Research, 2019)

Identification and Application of Roof Bed Separation (Water) in Coal Mines - Herong Gui; Manli Lin; Xiaomei Song (Mine Water and the Environment, 2018)

Atg7-Mediated Autophagy Is Involved in the Neural Crest Cell Generation in Chick Embryo - Guang Wang; En-ni Chen; Chang Liang; Jianxin Liang; Lin-rui Gao; Manli Chuai; Andrea Münsterberg; Yongping Bao; Liu Cao; Xuesong Yang (Molecular Neurobiology, 2018)

Tunable and Nontoxic Fluorescent Probes Based on Carbon Dots for Imaging of Indole Propionic Acid Receptor in Plant Tissues in Situ - Bixia Lin; Ying Yu; Fangfei Liu; Yujuan Cao; Manli Guo (Journal of Fluorescence, 2017)

Water-inrush mechanism research mining above karst confined aquifer and applications in North China coalmines - Herong Gui; Xiaomei Song; Manli Lin (Arabian Journal of Geosciences, 2017)

Pollution characteristics, source apportionment, and health risk of heavy metals in street dust of Suzhou, China - Manli Lin; Herong Gui; Yao Wang; Weihua Peng (Environmental Science and Pollution Research, 2017)

Types of water hazards in China coalmines and regional characteristics - Herong Gui; Manli Lin (Natural Hazards, 2016)

Heavy metals in deep groundwater within coal mining area, northern Anhui province, China: concentration, relationship, and source apportionment - Manli Lin; Weihua Peng; Herong Gui (Arabian Journal of Geosciences, 2016)

Construction and characterization of a transformation-competent artificial chromosome (TAC) library ofZizania latifolia (Griseb.) - Fan Na Kong; Shao Mei Jiang; Li Xue Shi; Cheng Li Song; Min De Jin; Shao Lin Jiang; Manli Weng; Bin Wang (Plant Molecular Biology Reporter, 2006)